cos(π/4-x)=-4/5得(√2/2)(cosx+sinx)=-4/5
所以cosx+sinx=-4√2/5 -----------(1)
cos(π/4+x)=sin(π/2-π/4-x)=sin(π/4-x)=-3/5(因为5π/4
所以cosx-sinx=-3√2/5 -----------(2)
(1)+(2)得2cosx=-7√2/5,得cosx=-7√2/10
(1)-(2)得2sinx=-√2/5,得sinx=-√2/10
所以tanx=sinx/cosx=1/7
sin2x=2sinxcosx=7/25
sin^x=1/50
(sin2x-2sin^2x)/(1+tanx)
=(7/25-2/50)/(1+1/7)
=21/100
cos(π/4-x)=-4/5 得 sinx+cosx =-4√2 / 5 (1)
联立sin²x+cos²x=1 得2sinxcosx=7/25 (2)
又因为5π/4<x<7π/4 ,
所以0<cosx- sinx,
所以cosx- sinx=3√2 / 5 (3)
化简(sin2x-2sin²x)/1+tanx =cosx (sin2x-2sin ²x) / cosx+sinx
=cosx(2sinxcosx-2sin²x)/cosx+sinx
=2sinxcosx(cosx-sinx)/cos+sinx
代入(1)(2)(3)式得原式=-21/100